Neurogenic Bladder in Children with Myelomeningocele - Aleksandar Sič; Borko Stojanović; Miroslav Đorđević (Diseases)
Myelomeningocele (MMC), a severe congenital anomaly resulting from neural tube closure defects, poses significant urological challenges necessitating specialized care. This review explores the intricate landscape of MMC within urological practice, advocating for a multidisciplinary approach to optimize patient outcomes. By surveying diverse treatment modalities, this review aims to offer insights into enhancing urological management strategies for MMC and guiding future research directions. At the heart of the conversation lies the pathophysiology of neurogenic bladder dysfunction in children with MMC, with a particular focus on the complexities of diagnosis and the various paradigms guiding urological management. Common complications such as recurrent urinary tract infections are examined alongside non-surgical interventions like intermittent catheterization (CIC) and pharmacotherapy, notably oxybutynin. Additionally, surgical options including botulinum toxin injection and reconstructive procedures are explored to enhance urological outcomes for affected children. By unpacking the complexities of neurogenic bladder dysfunction in MMC, this review emphasizes the imperative of a collaborative, multidisciplinary approach in urological care, ultimately aiming to enhance patient well-being and functional outcomes.